The first 50Myr of dinosaur evolution: macroevolutionary pattern and morphological disparity. - Brusatte, S; Benton, M; Ruta, M; Lloyd, G (2008)
The evolutionary radiation of dinosaurs in the Late Triassic and Early Jurassic was a pivotal event in the Earth's history but is poorly understood, as previous studies have focused on vague driving mechanisms and have not untangled different macroevolutionary components (origination, diversity, abundance and disparity). We calculate the morphological disparity (morphospace occupation) of dinosaurs throughout the Late Triassic and Early Jurassic and present new measures of taxonomic diversity. Crurotarsan archosaurs, the primary dinosaur 'competitors', were significantly more disparate than dinosaurs throughout the Triassic, but underwent a devastating extinction at the Triassic-Jurassic boundary. However, dinosaur disparity showed only a slight non-significant increase after this event, arguing against the hypothesis of ecological release-driven morphospace expansion in the Early Jurassic. Instead, the main jump in dinosaur disparity occurred between the Carnian and Norian stages of the Triassic. Conversely, dinosaur diversity shows a steady increase over this time, and measures of diversification and faunal abundance indicate that the Early Jurassic was a key episode in dinosaur evolution. Thus, different aspects of the dinosaur radiation (diversity, disparity and abundance) were decoupled, and the overall macroevolutionary pattern of the first 50Myr of dinosaur evolution is more complex than often considered.